Differentially Altered NMDAR Dependent and Independent Long-Term Potentiation in the CA3 Subfield in a Model of Anti-NMDAR Encephalitis - Blome, Roman; Bach, Willi; Guli, Xiati; Porath, Katrin; Sellmann, Tina; Bien, Christian G.; Köhling, Rüdiger; Kirschstein, Timo (Frontiers in Synaptic Neuroscience, 2018)
Purpose: Autoantibodies against NMDA receptors (NMDAR) in the cerebrospinal fluid (CSF) from anti-NMDAR encephalitis patients have been suggested to be pathogenic since in previous studies using patient CSF, NMDAR-dependent processes such as long-term potentiation (LTP) were compromised. However, autoantibodies may represent a family of antibodies targeted against different epitopes, and CSF may contain further autoantibodies. Here, we tested the specificity of the autoantibody by comparing NMDAR-dependent and NMDAR-independent LTP within the same hippocampal subfield, CA3, using CSF samples from four anti-NMDAR encephalitis patients and three control patients. Methods: We performed a stereotactic injection of patient-derived cell-free CSF with proven presence or absence of NMDAR-antibodies into the rat hippocampus in vivo. Hippocampal brain slices were prepared 1–8 days after intrahippocampal injection, and NMDAR-dependent LTP at the associational-commissural (A/C) fiber-CA3 synapse was compared to NMDAR-independent LTP at the mossy fiber (MF)-CA3 synapse. Results: The LTP magnitude at A/C fiber-CA3 synapses in slices from control-CSF-treated animals (168 ± 8% n = 54) was significantly higher than LTP in slices from NMDAR-CSF-treated animals (139 ± 9%, n = 40; P = 0.015), although there was some variation between the individual CSF samples. We found residual LTP in NMDAR-CSF-treated tissue which could be abolished by the NMDAR inhibitor D-AP5. Moreover, the CA3 field excitatory postsynaptic potential (fEPSP) was followed by epileptiform afterpotentials in 5% of slices (4/78) from control-CSF-treated animals, but in 26% of slices (12/46) from NMDAR-CSF-treated animals (P = 0.002). Application of the LTP-inducing paradigm increased the proportion of slices with epileptiform afterpotentials, but D-AP5 significantly reduced the occurrence of epileptiform afterpotentials only in NMDAR-CSF-treated, but not in control tissue. At the MF synapse, no significant difference in LTP values of control-CSF and in NMDAR-CSF-treated tissue was observed indicating that NMDAR-independent MF-LTP is intact in NMDAR-CSF-treated tissue. Conclusion: These findings indicate that anti-NMDAR containing CSF impairs LTP at the A/C fiber-CA3 synapse, although there is substantial variation among CSF samples suggesting different epitopes among patient-derived antibodies. The differential inhibition of LTP at this synapse in contrast to the MF-CA3 synapse suggests the specificity and underlines the pathophysiological role of the NMDAR-antibody.